1990
DOI: 10.1161/01.res.66.6.1681
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of canine epicardial electrogram. Short-term variations in the frequency content induced by myocardial ischemia.

Abstract: Power spectra of epicardial electrograms were studied in 13 anesthetized dogs subjected to occlusion of the left anterior descending coronary artery. Electrograms were obtained from a bipolar electrode placed on the epicardial surface of the left ventricle and recorded before and after coronary occlusion. After digitization, power spectra of the first and every 50th subsequent waveform were evaluated and compared with the power spectrum of the average waveform obtained from the baseline recording. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
3
16
1
Order By: Relevance
“…Other animal studies have shown similar results (Abboud, 1987; Abboud et al. , 1989, 1990; Mor‐Avi & Akselrod, 1990b).…”
Section: Hf‐qrs In Acute Myocardial Ischaemiasupporting
confidence: 77%
“…Other animal studies have shown similar results (Abboud, 1987; Abboud et al. , 1989, 1990; Mor‐Avi & Akselrod, 1990b).…”
Section: Hf‐qrs In Acute Myocardial Ischaemiasupporting
confidence: 77%
“…Although most of the ST elevation observed on an ischaemic body surface ECG (BRAUNWALD and SOBEL, 1992;NABEL et al, 1998;SCLAROVSKY, 1999) can be explained by ST elevation in the epicardial electrograms (MoR-AvI et al, 1990), our study shows that this is true, although to a lesser extent, for endocardial electrograms as well. This is apparent on inspection of the classification vector in the time domain for the immediate stage, which interestingly relates to the suggestion made by GARCIA et al (1998; 1999) that PCA-based indices better express the transformations undergone by the electrograms as a result of short-term ischaemia.…”
Section: Classification Vectorscontrasting
confidence: 51%
“…On the contrary, such a power shift toward the lower frequency range can be expected, considering the reduced conduction velocity caused by myocardial ischemia. 34 …”
Section: Anatomic Basis and Physiologic Import Of Abnormal High Frequmentioning
confidence: 99%
“…34 epicardial surface, caused variations in the high frequency waveforms similar to those produced by myocardial ischemia . 44 A cross correlation beat-to-beat analysis was applied to the high frequency waveforms and to the conventional electrocardiographic signals obtained during percutaneous transluminal coronary a n g i~p l a s t y .~~ Based on the results of this study, the morphology of the high frequency QRS complex is unequivocally more sensitive to transient myocardial ischemia than the conventional ECG.…”
Section: Morphology Of the High Frequency Qrs Waveformmentioning
confidence: 99%